Correlation between human neutrophil peptide 1-3 secretion and azurophilic granule (CD63) expression in early childhood caries - Muhammad Luthfi; Darmawan Setijanto; Markus Budi Rahardjo; Retno Indrawati; Priyawan Rachmadi; Mieke Sylvia Margaretha Amiatun Ruth; Yoes Prijatna Dachlan (Wolters Kluwer Medknow Publications, 2019)
Background: In saliva, neutrophil constitutes the most prominent first-line defense of immune cells against pathogenic microbes. The importance of neutrophils to the host immune systems of neutropenic or patients disabled with regard to their neutrophil function results in a tendency toward serious infections, such as early childhood caries (ECC). The cytoplasmic granules present in neutrophils play a major role in neutrophil-mediated inflammation. Azurophilic granules contain antimicrobial proteins, such as defensin, a human antimicrobial peptide (HNP 1-3). The aim of this study is to analyze the correlation of HNP 1-3 secretion with CD63 expression on the surface of salivary neutrophils. Materials and Methods: This study constituted a cross-sectional, analytical observational study. Saliva taken from preschoolchildren between the ages of 4-6 years who had been divided into two groups, i.e., early childhood caries group with decayed, extracted, filled teeth (def-t) index >6 and caries free with def-t = 0, was subjected to a HNP 1-3 secretion test using ELISA assay and an expression test for CD63 by means of a flow cytometry test. The results obtained were analyzed using independent t-test and Pearson correlation (P < 0.05). Results: The secretion of HNP 1-3 in the saliva of ECC was higher (172.6 ± 41.64) compared to that of caries-free cases (140.39 ± 31.91), whereas the level of CD63 salivary expression in ECC was lower (2.32 ± 0.57) than in the presence of caries (2.67 ± 0.46). Conclusion: In ECC cases, saliva increases HNP 1-3 secretion but decreases CD63 expression on the surface of salivary neutrophils.